Optimisasi Tween 80 dan Span 80 Sebagai Emulgator dalam Formula Krim Tabir Surya Kombinasi Ekstrak Etanol Daun Alpukat (Persea americana M.) dan Nanopartikel Seng Oksida Dengan Metode Simplex Lattice Design - Erindyah Retno Wikantyasning; Nabilla Indianie (STIKES MUHAMMADIYAH KLATEN, 2021)
Avocado leaves contain flavonoid which act as antioxidant whereas nanoparticles of zinc oxide can protect the skin against a wide spectrum of UV. The purpose of this study was to determine the effect of variation of Tween 80 and span 80 as emulsifier and determine the optimum formula of sunscreen scream containing ethanol extract of avocado leaves and zinc oxide nanoparticles. Avocado leaves were extracted by maceration method using ethanol. Nano zinc oxide is obtained by the High Energy Ball Milling technique and characterized using Particle Size Analyzer. Determination of the optimal cream formula with variations in the concentration of Tween 80 and Span 80 is done by Simplex Lattice Design (SLD) method. The maceration resulted ethanolic extract of avocado leaves with a yield of 34.4%. The synthesised zinc oxide nanoparticles obtained showed 179.47±5.98 nm in diameter. The results showed that increasing concentrations of Tween 80 and decreasing concentration of Span 80 increased spreadability but decreased the viscosity and adhesiveness of creams. The SPF evaluation of creams showed a medium protection category (SPF>15). The optimum formula was obtained with the ratio of Tween 80 and Span 80 was 7,8 and 3,2%, respectively, with the desirability value of 0.863.